Assessment of long-term hydrogeological changes and plausible solutions to manage hydrological extremes in the transnational Ganga River Basin - Surinaidu, L.; Amarasinghe, Upali; Maheswaran, R.; Nandan, M.J. (IWA Publishing, 2020)
The Ganga is an international transboundary river that flows across three major riparian countries: India, Nepal, and Bangladesh, where India shares a significant proportion of the total basin area. The river system is highly dynamic and regularly floods in all three countries due to abundant rainfall in a short period of only four months each year that causes tremendous loss of both property and human life. In this study, we have done a synoptic review to synthesize the hydrology, hydrogeology, and modeling studies that have analyzed hydrological changes and their impacts in the Ganga basin. This review also identifies some of the knowledge gaps and discusses possible options for enhancing the understanding of sustainable water development and management. This review indicated that transparent data sharing, use of satellite-based observations along with in-situ data, integrated hydro-economic modeling linked to reliable coupled surface–groundwater models, a central shared decision support center for early warning systems to deal with hydrological extremes, joint river commissions and monitoring teams, and multilateral water sharing treaties (agreements) are required to promote sustainable and equitable distribution of water resources and to avoid water sharing conflicts in the Ganga basin.